Digital Good Governance in Pesantren-Based Madrasas: A Conceptual Model - Langgeng Sutopo (Islamic Education Management Study Program, Faculty of Tarbiyah, Sunan Drajat Islamic Boarding School Institute, Lamongan, East Java, Indonesia., 2026)
This study aims to formulate a model of Good Governance of Islamic Boarding Schools in the management of Islamic education in Islamic boarding school-based madrasas in the digital era. Digital transformation has driven increased demands for transparency, accountability, and effectiveness of Islamic educational institutions, so a governance model is needed that is able to integrate the principles of good governance with the values of Islamic boarding schools. This study uses a qualitative approach with literature studies through systematic literature review with the stages of literature selection, thematic coding, concept synthesis, and comparative model formulation. The analysis was carried out through a targeted literature search, thematic grouping, comparison between findings, and concept synthesis to build a model. The literature used includes the study of education governance, Islamic education management, and digital transformation. The results of the study show that pesantren-based madrasah governance is hybrid, namely a combination of kiai authority, pesantren's collective culture, and modern management demands that work through the interaction between value logic, institutional structure, and digital system. Digitalization acts as a reinforcement in the aspects of transparency, accountability, data management efficiency, and stakeholder involvement through information system integration and institutional data standardization, although it is still faced with limited human resource capacity, cultural resistance, and institutional readiness. The novelty of this research lies in the effort to more fully assemble the four main elements, namely Islamic values, good governance principles, digital technology, and the institutional character of pesantren into one analytical framework that places pesantren as actors who participate in shaping the direction of transformation, not just recipients of change that have been fragmented in previous studies in the context of Indonesian pesantren so far.